2016
DOI: 10.1161/jaha.115.003019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hemoglobin Levels and Anemia on Mortality in Acute Stroke: Analysis of UK Regional Registry Data, Systematic Review, and Meta‐Analysis

Abstract: BackgroundThe impact of hemoglobin levels and anemia on stroke mortality remains controversial. We aimed to systematically assess this association and quantify the evidence.Methods and ResultsWe analyzed data from a cohort of 8013 stroke patients (mean±SD, 77.81±11.83 years) consecutively admitted over 11 years (January 2003 to May 2015) using a UK Regional Stroke Register. The impact of hemoglobin levels and anemia on mortality was assessed by sex‐specific values at different time points (7 and 14 days; 1, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
136
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(160 citation statements)
references
References 43 publications
12
136
2
2
Order By: Relevance
“…The strength of the association between anaemia and poor clinical outcome in our CVT cohort is similar to results of studies on arterial ischaemic stroke and haemorrhagic stroke [6]. Our study may have been underpowered to detect an association with mortality.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The strength of the association between anaemia and poor clinical outcome in our CVT cohort is similar to results of studies on arterial ischaemic stroke and haemorrhagic stroke [6]. Our study may have been underpowered to detect an association with mortality.…”
Section: Discussionsupporting
confidence: 82%
“…Outcome (mRS[3][4][5][6] in specific subgroups in the presence of anaemia CI, confidence interval; mRS, modified Rankin Scale; OR, odds ratio. Binary logistic regression analysis based on the pooled estimate after multiple imputation to account for missing variables.…”
mentioning
confidence: 99%
“…According to The Third National Health and Nutrition Examination Survey, the prevalence of World Health Organization‐defined anemia among community‐dwelling adults aged ≥65 years in the USA was 11.0% and 10.2% in men and women, respectively, rising to >20% in those >85 years . Contemporary literature in hospitalized patient populations mirrors these figures; in patients admitted with stroke (mean age ~78.0 years), anemia was present in ~25% of patients and indeed associated with high mortality …”
Section: Introductionmentioning
confidence: 99%
“…Comparisons with mentally healthy controls found that lower hemoglobin level could be an additional risk factor for circulatory mortality in BD. Strong evidence suggests that patients with anemia have increased mortality with cerebrovascular disease . The prevalence of anemia among chronic psychiatry patients is higher than the general population .…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence suggests that patients with anemia have increased mortality with cerebrovascular disease. 33 The prevalence of anemia among chronic psychiatry patients is higher than the general population. 34 Regular measures of hemoglobin of bipolar patients may be necessary to reliably detect associations between anemia and CVD mortality.…”
Section: Discussionmentioning
confidence: 99%